Causal linkages between supply chain management practices and performance: A balanced scorecard strategy map perspective. Issue 5 (1st June 2015) - Okongwu, Uche; BRULHART, Franck; Moncef, Btissam
Abstract : Purpose: – Today, supply chain design and management constitute a major source of competitive advantage for firms. The purpose of this paper is to empirically investigate, from a balanced scorecard strategy map (BSSM) perspective, the types of linkages through which supply chain management practices (SCMPs) impact on financial and non-financial performance, and consequently lead to the achievement of the firm's strategic objectives. Design/methodology/approach: – This study is carried out in two stages. First, based on the survey data collected from 450 French industrial firms (with a return rate of 20.2 per cent), structural equation modelling (SEM) is used to test eight hypotheses that are formulated through the discussion of previous theoretical and empirical findings in extant literature. Then, based on the framework of the BSSM, the SEM results are used to discuss the linkages between SCMPs and firm performance. Findings: – After confirming some of the relationships already observed in extant literature, the results show that there are many strategic paths (of different nature) that link SCMPs and other intangible assets to financial performance. Practical implications: – The results of the study constitute a practical contribution that would guide managers in the strategic alignment of their firm's supply chain initiatives with corporate strategy. The authors argue that when implementing supply chain management initiatives, managers should pay particular attention to how intangible assets act as mediating factors in the achievement of the firm's financial objectives. The BSC framework that the authors propose can also be used by researchers to investigate causal linkages between intangible and tangible assets. Originality/value: – There are few studies that adopt an extensive multidimensional approach by looking simultaneously at both upstream and downstream linkages of the supply chain whilst taking into account many performance measures. Using the BSSM framework, this paper proposes eight types of linkages that could lead to the achievement of the firm's strategic goals.